2020
DOI: 10.3390/en13092226
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of Thermal Energy Storage Integrated into Steam Power Plants

Abstract: For conventional power plants, the integration of thermal energy storage opens up a promising opportunity to meet future technical requirements in terms of flexibility while at the same time improving cost-effectiveness. In the FLEXI- TES joint project, the flexibilization of coal-fired steam power plants by integrating thermal energy storage (TES) into the power plant process is being investigated. In the concept phase at the beginning of the research project, various storage integration concepts were develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Often the impact of storage integration on flexibility can, however, be considered as too low in the hundred MW scale plants. The maximum load variation is below 5% in [70], for around 13% in [178] and with more extensive TES integration separately for high temperature reheated steam and lower temperature feed water regeneration up to 50% in [179]. Only in the smaller plants, such as industrial CHP, can the examples of larger load variation up to 100% be found as in the case of thermochemical storage in [180].…”
Section: Tes Systems For Cbmentioning
confidence: 98%
See 1 more Smart Citation
“…Often the impact of storage integration on flexibility can, however, be considered as too low in the hundred MW scale plants. The maximum load variation is below 5% in [70], for around 13% in [178] and with more extensive TES integration separately for high temperature reheated steam and lower temperature feed water regeneration up to 50% in [179]. Only in the smaller plants, such as industrial CHP, can the examples of larger load variation up to 100% be found as in the case of thermochemical storage in [180].…”
Section: Tes Systems For Cbmentioning
confidence: 98%
“…The addition of PCM to the tanks is proposed to improve the thermal capacity at the same volume. A drop in the pressure during the discharging of the tanks is another disadvantage [69,70]. For the CB applications, a similar size can be expected as that for similar systems for small steam parabolic trough flexible plants as 2 MW/6-24 MWh units [71].…”
Section: Reversible Rc Systemsmentioning
confidence: 99%
“…Cao et al [ 18 ] proposed an additional thermodynamic cycle, improving load flexibility by a separate turbine powered by a TES. Krüger et al [ 19 ] found that molten salt and solid medium TES can reduce the minimum load of a CFPP by 3–4%Pe, while the RTE ranges between 46 and 82 %. Above studies demonstrated the feasibility of integrating TES technologies in CFPPs to improve plant flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Such solid-based thermal energy storage systems also play a central role-in addition to the activities within the Energy Lab 2.0 project-in efficiency improvements and flexibilization of conventional [6,7] and solar thermal power plants [8,9] as well as in industrial processes [10,11]. In addition, these thermal storage options are key requirements in largescale electrical energy storage systems to achieve high efficiencies.…”
Section: Introductionmentioning
confidence: 99%